Kebudayaan dan Seni Adat Melayu Dialektika Islam Budaya Lokal dalam Perspektif Hukum Islam (Studi Kasus Tradisi Jamu Laut di Wilayah Pesisir Kabupaten Langkat) - Farif Habib (Peduli Riset dan Pengabdian Masyarakat, 2022)
Sea alms ceremony has indications that lead to shirk acts and rituals, namely doubling Allah SWT. The implementation of the sea banquet ceremony or sea alms is misinterpreted by people who lack the basic concept of Islam, namely promoting the values ​​of monotheism and the purity of the Muslim faith. Therefore, it is feared that it will damage the values ​​of monotheism if humans carry out these rituals. The results show that the phenomenon of the sea alms ceremony can be seen from the intentions of those who do it because it deals with issues of belief, aqidah, monotheism, faith, and how often this ceremony (for example once a month) is carried out because it is related to funds in the sense of idh'atul mal or tabdzir action is wasting property that is forbidden in religion. And also the history of this herbal medicine ceremony for Kwala Langkat Village, as a whole only understands the herbal medicine ceremony as a family tradition that must be maintained and carried out in the process. For the previous people, they had carried out according to the traditions left by their ancestors. This herbal medicine ceremony is considered as a cultural tradition that must be maintained and taught to the next generations, so that until whenever this herbal medicine ceremony will continue and become a tradition of the local community.